Poverty, Race, and New Directions in Child Welfare Policy - Dorothy E. Roberts (Washington University Journal of Law & Policy, 1999)
In this Essay I will present some of my early thoughts about how race and class affect recent shifts in federal child welfare policy.
Keywords: Child welfare